PENGARUH NON-PERFORMING FINANCING (NPF) TERHADAP RETURN ON ASSETS (ROA) PADA BANK MUAMALAT DI INDONESIA - Hamza, Amir; Ermaini; Suryani, Ade Irma (Jurnal Development, 2025)
This study aims to analyze the relationship between Non-Performing Financing (NPF) and Return on Assets (ROA) in Islamic banking institutions, focusing on Bank Muamalat Indonesia from 2007 to 2024. Using a quantitative approach and simple linear regression analysis, secondary data were collected from the bank's annual reports. The results indicate that although NPF theoretically influences ROA negatively, the statistical test showed no significant relationship between the two variables (p-value = 0.204, R2 = 9.87%). This implies that only a small proportion of ROA variation is explained by NPF, while other factors may have greater impact on profitability. The findings highlight a phenomenological gap between theory and empirical evidence, suggesting that NPF alone does not sufficiently determine the financial performance of Bank Muamalat. Therefore, it is recommended that future studies incorporate other variables and consider using nonlinear or more complex models to gain deeper insights into factors influencing bank profitability.